An Empirical Enquiry Of Bank Employees’ Emotional Intelligence And Their Satisfaction With Job (Journal of Namibian Studies : History Politics Culture, 2024)
Indian banking organizations are undergoing rapid changes due to technological advances. Emotional intelligence and job satisfaction are two important components in a business environment both are the object of several studies and provide focus on future and interesting research proposals (Papathanasiou & Siati, 2014). Therefore this study aims to examine the differences and relationship between employees’ emotional intelligence and their satisfaction with job in reference to Indian public and private sector banks. The purposive sampling technique was used and the participants of the study were 300 bank employees of both public and private sector banks in eastern cities of Uttar Pradesh, India. Data was collected through the self-reported questionnaire method. The findings of the study revealed that there is no significant difference in employees’ emotional intelligence, whereas a significant difference was observed in their satisfaction with job in public and private sector banks. Further, the correlation analysis suggested a significant positive relation between employees’ emotional intelligence and job satisfaction as well as results also revealed that dimension of emotional intelligence ‘regulation of emotion’ was a common significant positive predictor of employees’ job satisfaction in both public and private sector banks.